Persuasive Communication Strategy in Preventing Child Marriage through the Marriage Age Maturation Program in Sirau Village, Purbalingga Regency - Mumtingah, Suciarti; Iman Sulaiman, Adhi; Prastyanti, Shinta (PT ARRUS Intelektual Indonesia, 2024)
The purpose of this study is to persuasive communication strategy in preventing child marriage through the marriage age maturation program. This research is qualitative research that used the constructivism paradigm. The research was located in Sirau Village, Karangmoncol District, Purbalingga Regency. The selected unit of analysis is the implementation of the Marriage Age Maturation (PUP) program in Sirau Village, Purbalingga Regency. There are two types of data used in this research, namely primary data and secondary data. The primary data used are the results of observations and in-depth interviews. Secondary data from this research were obtained through library research and literature relevant to the research. The persuasive communication strategy carried out by BKKBN through the Marriage Age Maturation (PUP) program can be seen from activity groups in the form of Youth Family Development (BKR) and the Youth Counseling Information Center (PIK-R), Qualified Family Planning (PKB) instructors through clear message and creative media.